2019
DOI: 10.1017/qua.2019.57
|View full text |Cite
|
Sign up to set email alerts
|

Combining and competing effects between precipitation and temperature on Holocene fire regime evolution inferred from a sedimentary black carbon record in southwestern China

Abstract: Wildfires are sensitive to climate change, but their response to changes in temperature and precipitation on long timescales is still disputed. In this study, we present a ~9.4 ka black carbon mass sedimentation rate (BCMSR) record from Lake Ximenglongtan (XMLT), southwestern China, to elucidate the Holocene fire regime and its linkages to climatic conditions. The results indicate that the regional fire activity was low during the early Holocene (before 7.6 cal ka BP), increased notably at 7.6 cal ka BP, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
(164 reference statements)
0
2
0
Order By: Relevance
“…The increase in fire activity caused by intensified human activity during the late Holocene has been confirmed by many other studies of northern China (Huang et al, 2006;Wang et al, 2013;Miao et al, 2016;Mu et al, 2016;Pang et al, 2021) and elsewhere (Ning et al, 2020;Barhoumi et al, 2021). For example, Wang et al (2013) proposed that fire activity increased significantly in the Daihai Lake region during the late Holocene, possibly linked to an increase in human activity after ~2300 yr BP.…”
Section: Effects Of Human Activities On the Fire-climate Relationship...mentioning
confidence: 58%
See 1 more Smart Citation
“…The increase in fire activity caused by intensified human activity during the late Holocene has been confirmed by many other studies of northern China (Huang et al, 2006;Wang et al, 2013;Miao et al, 2016;Mu et al, 2016;Pang et al, 2021) and elsewhere (Ning et al, 2020;Barhoumi et al, 2021). For example, Wang et al (2013) proposed that fire activity increased significantly in the Daihai Lake region during the late Holocene, possibly linked to an increase in human activity after ~2300 yr BP.…”
Section: Effects Of Human Activities On the Fire-climate Relationship...mentioning
confidence: 58%
“…Mu et al (2016) showed that fires linked to agriculture may have led to increased biomass burning associated with agricultural activity after ~2000 yr BP in the Horqin Sandy Land in southeastern Inner Mongolia. In addition, although the Holocene evolution of fires in southwestern China differs from that in northern China, Ning et al (2020) suggested that the higher fire occurrence in the region over the past 2200 years was likely related to intensified human activities.…”
Section: Effects Of Human Activities On the Fire-climate Relationship...mentioning
confidence: 99%